Restless legs syndrome related to hemorrhage of a thoracic spinal cord cavernoma. (4th March 2018) - Hamdaoui, Malik; Ruppert, Elisabeth; Comtet, Henri; Kilic-Huck, Ulker; Wolff, Valérie; Bataillard, Marc; Bourgin, Patrice
Abstract : Context: Restless legs syndrome (RLS) is a common neurological disorder characterized by an irresistible urge to move the lower limbs often accompanied by unpleasant sensations in the legs, worsened at rest and in the evening. Symptoms are improved by movement. Its pathophysiology remains poorly understood. Lesion-related RLS has been reported, mainly in cases of stroke-related RLS involving the brainstem and lenticulostriate nuclei. Only few data of RLS in a context of spinal cord injury have been reported. Findings: We report the case of a woman with secondary RLS due to hemorrhage of a spinal cord cavernoma located at T9-T10. Following recovery from the acute phase of the hemorrhage, the patient began to complain about restlessness in her legs causing impaired sleep and daytime somnolence. Polysomnographic investigations found a high index of periodic leg movements during sleep (71/hour), but no sleep disordered breathing. Iron stores were normal. Relief of symptom's severity was obtained with gabapentin 600mg in the evening. Conclusion/Clinical Relevance: We hypothesize a possible involvement of the diencephalospinal pathway in the patient's RLS pathophysiology. A systematic study of focal lesions associated with RLS may contribute to improving our understanding of the pathophysiological mechanisms underlying this condition. The frequency of RLS associated with lesions of the spinal cord might be underestimated. Clinicians should be aware of spinal cord lesion-related RLS, especially as efficient treatments are available.